Rethinking of Local Autonomy and Fiscal Decentralization Policy: Can It Improve The Quality of Human Capital? A Case in Eastern Region of Indonesia - Fahmi Prayoga; Candra Fajri Ananda (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2023)
Purpose This study aims to see the effect of regional autonomy and fiscal decentralization in the fields of education, health, and the economy in the development of human resources in Eastern Indonesia. Design/methodology/approach This study uses a quantitative approach with panel data regression utilizing data from 16 provinces in Eastern Indonesia from 2010-2019. Findings According to the results, the development of human resource quality is influenced by government spending on education, health, and GRDP per capita. However, the study reveals that capital expenditure does not play a significant role in the enhancement of human resource quality. Research limitations/implications One shortcoming of this research is its lack of detailed information regarding how capital expenditures, education expenditures, and health expenditures are distributed across various local governments. Originality/value This study shows the impact of fiscal decentralization and regional autonomy by comparing the results gap that occurs between the western and eastern regions of Indonesia on human resource development